2013
DOI: 10.1016/j.rasd.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The double ABCX model of family adaptation in families of a child with an autism spectrum disorder attending an Australian early intervention service

Abstract: , T. (2013). The double ABCX model of family adaptation in families of a child with an autism spectrum disorder attending an Australian early intervention service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 63 publications
9
60
2
2
Order By: Relevance
“…These include stressors (aA) comprising child characteristics such maladaptive behaviour (Hall and Graff 2012;Manning et al 2011;Pakenham et al 2005;Paynter et al 2013), ASD symptom severity (Stuart and McGrew 2009), adaptive functioning (Hall and Graff 2011), and a pile-up of family demands (i.e., factors outside of the parent-child relationship ;Bristol 1987;Pakenham et al 2005;Stuart and McGrew 2009) which predict negative outcomes in families raising children with ASD. Studies have also identified social support (Bristol 1987;Kaniel and SimanTov 2011;Manning et al 2011;Siman-Tov and Kaniel 2011;Stuart and McGrew 2009;Paynter et al 2013;Pozo et al 2013) as a useful resource, which corresponds with the 'bB' component of the Double ABCX model that may buffer the effects of these stressors. In addition, the use of positive appraisals (Manning et al 2011) and a greater sense of coherence (i.e., the ability to view a situation as significant, predictable, and able to be managed; Kaniel and Siman-Tov 2011;Pozo et al 2013), 'cC' components, have demonstrated positive relationships with parental wellbeing.…”
Section: Applying the Double Abcx Model To Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…These include stressors (aA) comprising child characteristics such maladaptive behaviour (Hall and Graff 2012;Manning et al 2011;Pakenham et al 2005;Paynter et al 2013), ASD symptom severity (Stuart and McGrew 2009), adaptive functioning (Hall and Graff 2011), and a pile-up of family demands (i.e., factors outside of the parent-child relationship ;Bristol 1987;Pakenham et al 2005;Stuart and McGrew 2009) which predict negative outcomes in families raising children with ASD. Studies have also identified social support (Bristol 1987;Kaniel and SimanTov 2011;Manning et al 2011;Siman-Tov and Kaniel 2011;Stuart and McGrew 2009;Paynter et al 2013;Pozo et al 2013) as a useful resource, which corresponds with the 'bB' component of the Double ABCX model that may buffer the effects of these stressors. In addition, the use of positive appraisals (Manning et al 2011) and a greater sense of coherence (i.e., the ability to view a situation as significant, predictable, and able to be managed; Kaniel and Siman-Tov 2011;Pozo et al 2013), 'cC' components, have demonstrated positive relationships with parental wellbeing.…”
Section: Applying the Double Abcx Model To Asdmentioning
confidence: 99%
“…In addition, the use of positive appraisals (Manning et al 2011) and a greater sense of coherence (i.e., the ability to view a situation as significant, predictable, and able to be managed; Kaniel and Siman-Tov 2011;Pozo et al 2013), 'cC' components, have demonstrated positive relationships with parental wellbeing. Finally, avoidance coping (Paynter et al 2013;Stuart and McGrew 2009) and behavioural disorganisation (Pakenham et al 2005) have been found to influence poor adaptation in families raising children with ASD (i.e., 'BC' components of the Double ABCX model).…”
Section: Applying the Double Abcx Model To Asdmentioning
confidence: 99%
“…For example, substantial evidence indicated that family support reduced care-giver burden in families with a child with ASD [20,29] and that family and neighbourhood support was associated with improved parental mental health [20,30,31] and reduced parental aggravation or irritability [32]. Further substantial evidence [33] [as classified by our descriptors on Table 1] was provided using the Multidimensional Scale of Perceived Social Support (MSPSS) which indicated that greater social support was associated with lower levels of individual distress (apart from anxiety and depression) in the families of children with ASD [25]. Alternatively, substantial evidence demonstrated that mothers of children with ASD had poorer mental health than other mothers but no less social support for parenting [34].…”
Section: Level Of Supportmentioning
confidence: 99%
“…Researchers provided substantial evidence that the social impact of the child's disability [18] and challenging behaviours [19][20][21][22][23][24][25] in children with ASD or ID was associated with poorer care-giver mental health. At the same level of evidence, challenging child behaviours in children with ID were related to poorer care-giver physical health in subsequent years [26].…”
Section: Challenging Child Behaviormentioning
confidence: 99%
“…Studies also found significant associations between greater use of active-avoidance coping strategies with higher levels of depression, stress, and parenting stress (Paynter et al, 2013).…”
Section: Introductionmentioning
confidence: 97%